The capacity-building outlook in the Atlantic - Seabra, Pedro; Costa, Rita (The capacity-building outlook in the Atlantic, 2022)
Capacity-building has become a bona fide buzzword in policy circles. Imbued with the promise of incorporating local demands while fostering international engagementthrough limited but valuable technical expertise to regions and countries in need, the concept has been quickly elevated to the forefront of debate. This, in turn, has contributed to shift “the emphasis towards more fluid approaches to solve societal problems, relying on technology, knowledge and expertise rather than clearly stated objectives, one-size-fits-all solutions, and top-down approaches” (Bueger & Tholens 2021, p. 22). At the same time, it has led to an increase in the number of organisations and platforms seeking to implement what is often enough a loosely-defined playbook. In this context, new multilateral initiatives have purported to assume a role of their own in the capacity-building domain. However, how to better translate such goals into practice remains open for discussion. This report seeks to build upon a set of key lessons learned from previous endeavours in order to best depict and summarize the challenges that the current Atlantic outlook provides in the capacity-building domain.The ensuing work is grounded by two key goals: (1) to link existing debates over the perils and potentials of the capacity-building concept with practical needs, while retaining a focus on the Atlantic space; (2) and to ensure that valid entry-points are identified for further action by interested parties, while grounded in existing assessments over the effectiveness of capacity-building programs.